ANALISIS KARAKTER GOTONG ROYONG DALAM IMPLEMENTASI MODEL PEMBELAJARAN PROJECT- BASED LEARNING (PJBL) UNTUK MEWUJUDKAN PROFIL PELAJAR PANCASILA - Novanda Fanny Relisti; Fajar Setiawan; Badruli Martati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
His research aims to analyze the mutual cooperation character of elementary school students in the implementation of the Project-Based Learning (PjBL) learning model to realize the Pancasila Student Profile, this is one of the innovative approaches that is able to integrate material mastery with student character building through project completion activities. The approach used is descriptive qualitative, with data collection techniques in the form of observation, interviews, and questionnaires. The results showed that the implementation of the PjBL model achieved students' mutual cooperation character. Students are able to work together in groups. Shared responsibility is seen from students' initiatives in helping group members. Social care is reflected in the empathetic attitude of students who support group friends. In addition, students show the behavior of respecting each other's opinions. Solidarity also increased, as seen from students' efforts to support each other for the success of the group. This research indicates that PjBL can be a relevant learning strategy to instill mutual cooperation values that are in line with the Pancasila Student Profile.